(untitled) (Research, Society and Development, 2022)
Objective: To compare the prevalence of anogenital infection by human papillomavirus (HPV) in immunobiological users being treated for immune-mediated chronic inflammatory diseases with that in non-users. Methodology: The total sample studied consisted of 228 participants divided into 2 groups: 114 users and 114 non-users of immunobiological, cytotoxic or corticosteroid therapy, with non-psoriasis dermatoses and non-HPV predisposing conditions. Both groups were evaluated clinically and by polymerase chain reaction (PCR). Results: The prevalence of low-risk HPV in the immunobiological user and non-user groups was 8/49 (16,3%) and 3/29 (10,3%), respectively (p=0.524). The low-risk types found were HPV 6, 11, 40, 42 and 44. The prevalence of high-risk HPV was 23/114 (20,2%) in the users versus 21/114 (18,4%) in the non-users (p=0.737), distributed according to the following types: HPV 16 (3/228 – 1,3%), 18 (5/228 – 2,2%), and non-16/18 (36/228 – 15,8%). After pairing by sex and age, the prevalence of high-risk HPV was 13/62 (21,0%) and 8/62 (12,9%) for immunobiological users and non-users, respectively (p=0.231). Conclusion: The prevalence of anogenital HPV infection in patients with immune-mediated chronic inflammatory diseases treated with immunobiologicals is similar to that in non-users.